Sensitive luminescence mechanochromism and unique luminescence thermochromism tuned by bending the P–O–P skeleton in the diphosphonium/iodocuprate(i) hybrid. Issue 27 (23rd June 2022) - Yang, Zhen-Cong; Song, Kai-Yue; Zhou, Pan-Ke; Zong, Lu-Lu; Li, Hao-Hong; Chen, Zhi-Rong; Jiang, Rong
Abstract : The unique luminescence mechano/thermochromism of a diphosphonium/iodocuprate(i ) hybrid is led by the mechanically induced adjustments in cuprophilic interactions and bent P–O–P backbone upon heating. Abstract : Two new copper(i ) iodide-based hybrids, i.e. (Py3 P–O–PPy3 )(Cu2 I4 ) (1 ) and (Py3 P–O–PPy3 )(Cu4 I6 ) (2 ) (Py = pyrrolidine), have been prepared, in which the tripodal diphosphonium (Py3 P–O–PPy3 ) 2+ is in situ generated in the one-pot synthesis. The disordered (Cu4 I6 ) 2− tetramers are rare with two sets of tetracuprate centers. Interestingly, 1 exhibits sensitive luminescence mechanochromism, which is ascribed to the disturbed cuprophilic Cu⋯Cu interactions and the crystalline packing adjustment by destroying C–H⋯I hydrogen bonds during mechanical force. In particular, the luminescence thermochromism is unique, whose fluorescence intensity is strengthened with the elevated temperature. This could be due to the S 2 – S 1 internal conversion on the linear P–O–P backbone, which will be bent upon heating. Simultaneous luminescence thermo/mechanochromism can also be monitored in 1 . However, no luminescence thermo/mechanochromic performances can be detected in 2, so the luminescence thermo/mechanochromism of 1 could be quenched with DMF. The conclusions in this work might provide a new large-scale synthesis strategy for intelligent responsive luminescent materials.